Multi-physics methodology for phase change due to rapidly depressurised two-phase flows. (November 2021) - Chávez-Modena, M.; Rubio, G.; Valero, E.; Mira, D.; Lehmkuhl, O.
Highlights: CFD methodology to couple with a Zonal modelling for fire-extinguishing systems. Atomization characterization of Novec-1230 agent through a nozzle. A multiphase conservative level set LES predicts the primary breakup atomization. A particle based/URANS method solves the spreading of the agent and phase change. Abstract: Zonal modeling is a common technique for the numerical certification of fire-extinguishing systems, however it is not valid to simulate the complex physical phenomena that occurs near the agent injection. We present a multi-scale method for the accurate generation of inflow boundary conditions valid for zonal modeling based on the description of the phase change of a rapidly depressurised mist of a fire suppression system. The generation of accurate boundary conditions includes the characterization of the injection of the fire suppression agent from atomization to evaporation and mixing. The multi-scale methodology is based on the use of a high fidelity multiphase conservative level set LES for the characterization of the nozzle to develop an empirical model for primary breakup. Secondly, a low fidelity particle-based method with phase change and unsteady RANS is used for parametric studies. This multi-scale approach requires an affordable computational effort. The multi-scale methodology is tested in a system consisting of a pressurised fire extinguishing agent (Novec-1230) that is injected into the ambient through a nozzle that produces the atomization of the agent. The accuracy of the developed approach is compared with the experimental data.